Exogenous Ca2+ priming can improve peanut photosynthetic carbon fixation and pod yield under early sowing scenarios in the field - Song, Qiaobo; Zhang, Siwei; Bai, Chunming; Shi, Qingwen; Wu, Di; Liu, Yifei; Han, Xiaori; Li, Tianlai; Yong, Jean Wan Hong (Frontiers in Plant Science, 2022)
Harnessing cold-resilient and calcium-enriched peanut production technology are crucial for high-yielding peanut cultivation in high-latitude areas. However, there is limited field data about how exogenous calcium (Ca2+) application would improve peanut growth resilience during exposure to chilling stress at early sowing (ES). To help address this problem, a two-year field study was conducted to assess the effects of exogenous foliar Ca2+ application on photosynthetic carbon fixation and pod yield in peanuts under different sowing scenarios. We measured plant growth indexes, leaf photosynthetic gas exchange, photosystems activities, and yield in peanuts. It was indicated that ES chilling stress at the peanut seedling stage led to the reduction of Pn, gs, Tr, Ls, WUE, respectively, and the excessive accumulation of non-structural carbohydrates in leaves, which eventually induced a chilling-dependent feedback inhibition of photosynthesis due mainly to weaken growth/sink demand. While exogenous Ca2+ foliar application improved the export of nonstructural carbohydrates, and photosynthetic capacity, meanwhile activated cyclic electron flow, thereby enhancing growth and biomass accumulation in peanut seedlings undergoing ES chilling stress. Furthermore, ES combined with exogenous Ca2+ application can significantly enhance plant chilling resistance and peanut yield ultimately in the field. In summary, the above results demonstrated that exogenous foliar Ca2+ application restored the ES-linked feedback inhibition of photosynthesis, enhancing the growth/sink demand and the yield of peanuts.